2023
DOI: 10.1002/1878-0261.13379
|View full text |Cite
|
Sign up to set email alerts
|

Tetraploidy‐linked sensitization to CENP‐E inhibition in human cells

Abstract: Tetraploidy is a hallmark of cancer cells, and tetraploidy‐selective cell growth suppression is a potential strategy for targeted cancer therapy. However, how tetraploid cells differ from normal diploids in their sensitivity to anti‐proliferative treatments remains largely unknown. In this study, we found that tetraploid cells are significantly more susceptible to inhibitors of a mitotic kinesin (CENP‐E) than are diploids. Treatment with a CENP‐E inhibitor preferentially diminished the tetraploid cell populati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We speculate that these differences arise due to divergent time-dependent changes of microtubule stability 78,97 after mitotic prolongation between chromosomally unstable cancer cells and non-transformed cells, which could preclude initiation of congression in the absence of CENP-E specifically in these cancers. Interestingly, since it was recently shown that tetraploid cells are significantly more susceptible to CENP-E inhibitors 98 and to perturbation of the Kif18a motor 99 compared to their diploid counterparts, we hypothesize that these observations could be part of a common theme of divergent responses of chromosomally stable and unstable cells to mitotic prolongation. We envisage that these divergent responses are the result of faulty chromosome congression and SAC activation in chromosomally unstable cells, which could be a valuable path to explore in the development of new tumor treatment strategies specifically targeting aneuploid cells.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We speculate that these differences arise due to divergent time-dependent changes of microtubule stability 78,97 after mitotic prolongation between chromosomally unstable cancer cells and non-transformed cells, which could preclude initiation of congression in the absence of CENP-E specifically in these cancers. Interestingly, since it was recently shown that tetraploid cells are significantly more susceptible to CENP-E inhibitors 98 and to perturbation of the Kif18a motor 99 compared to their diploid counterparts, we hypothesize that these observations could be part of a common theme of divergent responses of chromosomally stable and unstable cells to mitotic prolongation. We envisage that these divergent responses are the result of faulty chromosome congression and SAC activation in chromosomally unstable cells, which could be a valuable path to explore in the development of new tumor treatment strategies specifically targeting aneuploid cells.…”
Section: Discussionmentioning
confidence: 86%
“…We propose that the duration of mitosis influences the stability of kinetochore microtubules (Bakhoum et al, 2009;Kabeche & Compton, 2013) in a manner that impedes congression initiation specifically in CENP-E-deficient cancer cells compared to non-transformed cells during prolonged mitosis. Recent studies have shown that tetraploid cells are more vulnerable to CENP-E inhibitors (Yoshizawa et al, 2023) and Kif18a inhibitors (Quinton et al, 2021) than diploid cells, likely due to their prolonged mitotic duration (Gliech et al, 2024). We hypothesize that these differential effects of kinesin inhibitors stem from distinct responses to mitotic prolongation between chromosomally stable and unstable cells.…”
Section: Discussionmentioning
confidence: 99%
“…An essential kinetochore protein, CENP-E moves mono-oriented chromosomes to the spindle equator, mediating congression 51,71,72 . Strikingly, tetraploid cancers are far more susceptible to CENP-E inhibitors than diploids 5254,73,74 .…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, tetraploid cancers are far more susceptible to CENP-E inhibitors than diploids [52][53][54]73,74 .…”
Section: Meiotic and Ion Homeostasis-related Phenotypic Shifts Upon Wgdmentioning
confidence: 99%
“…The combination of GSK923295 and pharmacologic inhibitors of mitogen-activated ERK kinase (MEK1/2) shows a significant synergistic growth inhibition on neuroblastoma, lung, pancreatic, and colon carcinoma cell lines, which further results in mitotic arrest and apoptosis (Mayes et al, 2013). GSK923295 significantly inhibits the proliferation of tetraploid cells compared with diploids, suggesting superior generality of CENP-E-targeted tetraploidy inhibition (Yoshizawa et al, 2023). These findings indicate that in cancer treatment, exploring the combination of GSK923295 with other antitumor drugs might improve its clinical application.…”
Section: Gsk923295 and Its Derivativesmentioning
confidence: 99%